Kesejahteraan Spiritual dan Kualitas Hidup di antara Lansia yang Dilembagakan: Studi Korelasi - Syarli, Setiadi; Jepisa, Tomi; Mahmudah, Rifahatul; Ririn, Ririn; Husni, Husni (Pustaka Galeri Mandiri, 2026)
The increasing number of older adults in Indonesia poses challenges in maintaining physical, psychological, social, and spiritual well-being. One important factor influencing the quality of life of older adults, especially those living in social care institutions, is spiritual well-being, which includes the relationship with God and a sense of meaning in life. This study aimed to examine the relationship between spiritual well-being and the quality of life of older adults at Tresna Werdha Social Care (TWSC) Kasih Sayang Ibu Batusangkar and TWSC Sabai Nan Aluih Sicincin. This study employed a quantitative correlational analytic design with a cross-sectional approach. The study population consisted of all older adults residing in the two TWSCs, totaling 180 individuals, using a total sampling technique. The instruments used were the Spiritual Well-Being Scale (SWBS) and the Indonesian version of WHOQOL-BREF. Data analysis was conducted using univariate and bivariate methods, with the Chi-square test at a significance level of 0.05. The results showed that most older adults had a high level of spiritual well-being (67.2%) and a good quality of life (63.3%). Statistical analysis indicated a significant relationship between spiritual well-being and quality of life among older adults (p = 0.000; OR = 3.4; 95% CI = 2.1–5.7). Older adults with high spiritual well-being were 3.4 times more likely to have a good quality of life compared to those with low spiritual well-being. Spiritual well-being plays an important role in improving the quality of life of older adults in social care institutions. The spiritual dimension helps older adults achieve inner peace, find meaning in life, and strengthen social relationships. Therefore, the implementation of spirituality-based nursing interventions and the strengthening of routine religious activities in social care institutions are necessary to enhance the holistic well-being of older adults